From Awareness to Risk Prevention: Developing Messages for Crisis Communication During Pandemics and Infodemics - Hasanah , Fadhiilati; Destrity, Nia Ashton (Jurnal Komunikasi, 2024)
This study aims to describe the crisis communication messages delivered by Kawal COVID-19 via Instagram social media in the pre-crisis and early crisis stages to deal with the pandemic and infodemic in Indonesia. Qualitative content analysis was conducted on 190 posts by the Instagram account @kawalcovid19.id on March 1-May 24, 2020. The results of the study showed that the crisis and risk communication delivered were in the form of sensemaking messages (awareness/understanding), possible risks and potential crises that would occur, and education related to the COVID-19 virus. Efficacy messages (efficacy/success) were also presented. This study also found a combination of sensemaking and efficacy messages and linked them to the social and cultural context. Other messages related to identity and public relations strategies were used to build credibility and interactivity with the public.